Studies on digital holography for aspheric surface measurement - Wang, Zhaomin (2017)
Digital holography is fast becoming a generalized technique for 3D precision measurement. By numerical reconstruction and propagation of a digital hologram, the optical field from an object and thus the amplitude and phase can be quantitatively reconstructed. The quantitative phase allows determination of the surface topography of the object with nanometer sensitivity. Aspheric lenses are being increasingly used in optical system due to savings in costs and components. However, an aspheric is a complex surface designed using non-linear equations and hence fabrication is as best as can be measured. Various approaches primarily using null interferometry have been proposed and used with limited success and slow speeds. In this thesis, measurement and characterization of the aspheric lens with digital holography is studied. An adaptive optical element is introduced in the digital holography setup to measure aspheric lenses with different Numerical Aperture (NA). To measure the high gradient surface on the aspheric lens, a Dual-Wavelength Digital Holography (DWDH) with four phase unwrapping methods is proposed and demonstrated. For high resolution and large Field Of View (FOV), a novel synthetic aperture digital holography with first order spectrum based registration is suggested and analyzed. Finally, to characterize aspheric lenses, a linear simplified expression is applied to aspheric surface fitting, and a modified Zernike polynomials fitting method is proposed to evaluate the wavefront of the aspheric lens.